Social Identity in a Multi-Ethnic Society - Al-Amiri, M. M. Ali Malih Mahdi; Suleimani, Esmaiel (Journal of Cultural Analysis and Social Change, 2026)
The present study aims to: 1. Identify the level of social identity among university students. 2. Determine the extent of differences in social identity according to the variable of gender (male–female). 3. Examine the degree of differences in social identity according to ethnicity (Turkmen, Arab, Kurdish). To achieve the objectives of the current study, the researcher constructed a Social Identity Scale using the descriptive method and based on Social Identity Theory by Tajfel (1969) and Tajfel & Turner (1979). After administering the scale to a representative sample of university students consisting of (400) male and female participants, the results revealed the following: 1. University students possess a high level of social identity. 2. There are statistically significant differences between the two independent samples according to gender, in favor of females. 3. Regarding differences among ethnicities, the study found that: There are no statistically significant differences in the sense of social identity among the three ethnic groups (Turkmen, Arab, Kurdish).